Penetrance of Parkinson’s disease in GBA1 carriers depends on variant severity and polygenic background - Emadeldin Hassanin; Zied Landoulsi; Sinthuja Pachchek; NCER-PD Consortium; Peter Krawitz; Carlo Maj; Rejko Krüger; Patrick May; Dheeraj Reddy Bobbili (npj Parkinson's Disease)
Abstract Heterozygous GBA1 variants increase Parkinson’s disease (PD) risk with variable penetrance. We investigated the interaction between genome-wide polygenic risk scores (PRS) and severity of pathogenic GBA1 variants (GBA1 PVs) to assess their combined impact on PD risk. GBA1 variants were identified from whole exome sequencing in the UK Biobank and targeted PacBio sequencing in the Luxembourg Parkinson’s Study, with PRS calculated using genome-wide significant SNPs. GBA1 PVs were present in 8.8% of PD patients in the UK Biobank and 9.9% in LuxPark, with carriers showing consistently higher PD risk across all PRS categories. In the highest PRS category, PD risk increased 2.3-fold in the UK Biobank and 1.6-fold in LuxPark. Severe and mild GBA1 variants conferred nearly double the risk of PD compared to risk variants. Our findings demonstrate the impact of PRS on GBA1 PVs penetrance, highlighting implications for genetic counseling and clinical trial design in GBA1-associated PD.